HIF-1 — a big chapter in the cancer tale - Ajduković, J. (Experimental Oncology, 2016)
Approximately 1.0–1.5% of the genome is transcriptionally regulated by hypoxia, and hypoxia-inducible factor (HIF)-1α is the transcription factor modulating many of these genes. Cancer cells are able to survive hypoxic environments and hypoxia itself can activate adaptive cellular responses that contribute to tumor progression. Many HIF-1α-mediated biological effects are beneficial for tumor progression, including metabolic shift toward glycolysis, inhibition of fatty acid β-oxidation, production of cellular reactive oxygen species and altering expression of tumor suppressor genes. HIF-1 promotes selective mitochondrial autophagy, resis- and altering expression of tumor suppressor genes. HIF-1 promotes selective mitochondrial autophagy, resistance to T cell mediated lysis of cancer cells, induction of pluripotent cancer stem cells, epithelial-mesenchymal and epithelialmesenchymal-endothelial transitions beneficial for tumor growth and progression, loss of E-cadherin. HIF-1 also induces production of signal molecules and cytokines by carcinoma-associated fibroblasts and upregulation of certain microRNAs important for cancer progression. This minireview focuses on the HIF-1 promoting role in tumor initiation and progression and HIF-1 targeting. HIF-1 pathway downregulation seems to be promising in future cancer treatment.